Development of an Experiential-Contextual Teaching and Learning (ECTL) Model for Entrepreneurship Education in Vocational Higher Education - Wesnita, Alvia; Zamil, Ilham (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop and evaluate the validity, practicality, and effectiveness of an Experiential-Contextual Teaching and Learning (ECTL) model for entrepreneurship education in vocational higher education. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation phases. The ECTL model was designed based on five instructional syntax phases: concrete experience, observation and reflection, abstract conceptualization, meaningful learning, and active experimentation. The model was supported by a lecturer guidebook, student guidebook, syllabus, and semester learning plans. The validity of the model and its supporting products was evaluated by five experts using Aiken’s V coefficient, with a minimum acceptable value of 0.600. Practicality was assessed through small-scale trials involving five students and two lecturers, followed by expanded-scale trials involving 29 students in the experimental group and 29 students in the control group. Effectiveness was examined through cognitive pretest–posttest assessments, affective observation rubrics, and psychomotor performance rubrics. The data were analyzed using the Kolmogorov–Smirnov normality test, Levene’s homogeneity test, and independent-samples t-tests at a significance level of 0.05. The results indicated that all developed products achieved Aiken’s V values above the minimum threshold, ranging from 0.80 to 0.88, confirming their validity. The practicality evaluation demonstrated very high levels of usability, with lecturer response scores ranging from 92.4% to 96.1% and student response scores ranging from 85.06% to 85.53%. The experimental group achieved a significantly higher mean posttest score (80.00) than the control group (73.24), with t(56) = 3.212, p = 0.002. Furthermore, affective and psychomotor assessments revealed that 96.6% of students attained good or very good performance levels. All students (100%) successfully met the passing criteria, and 44.8% achieved the highest grade (A). These findings indicate that the ECTL model is valid, highly practical, and effective for entrepreneurship education in vocational higher education. Therefore, it is recommended as an alternative to conventional teacher-centered instructional approaches.